Design and Construction on A simple Magnifying Glass Using Recycled Bottles. - Mbonyimukiza, Andrew (Kabale University, 2023)
Human eyes have limitations of visibility because not all objects in focus give brighter and sharper images needed to access quality. Some objects appear smaller. In order to view smaller objects, a magnifying glass is used to make the objects bigger to the eye hence it can reduce the cost of purchasing spectacles. Therefore, the project is about design and construction of a simple magnifying glass using recycled bottles (relatively equal disc cuttings), glue, syringe, a sharp knife, a pair of scissors, left over part of cello tape or bottle top made hollow and a marker.